2014
DOI: 10.1634/theoncologist.2014-0120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of Above-Standard Dose of Octreotide LAR in Patients With Neuroendocrine Tumors for Control of Carcinoid Syndrome Symptoms: A Multicenter Retrospective Chart Review Study

Abstract: Background. Octreotide LAR is used in patients for control of carcinoid syndrome (CS) and other symptoms of hormone hypersecretion. The aim of this study was to examine reasons for octreotide LAR dose escalation and observe CS symptom improvement in patients with neuroendocrine tumors (NETs) who underwent octreotide LAR dose escalation at three cancer referral centers. Methods. Medical records for patients with diagnosis of carcinoid or pancreatic NET who had received one dose or more of octreotide LAR above 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 16 publications
2
73
0
Order By: Relevance
“…This is in contrast to retrospective studies that have shown that patients with refractory carcinoid syndrome achieve symptom control by increasing dose ofoctreotide LAR beyond 30 mg [14,17]. These data are in line with consensus guidelines recommending titration of octreotide LAR dose beyond 20-30 mg as required for symptom control.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in contrast to retrospective studies that have shown that patients with refractory carcinoid syndrome achieve symptom control by increasing dose ofoctreotide LAR beyond 30 mg [14,17]. These data are in line with consensus guidelines recommending titration of octreotide LAR dose beyond 20-30 mg as required for symptom control.…”
Section: Discussionsupporting
confidence: 77%
“…While the PROMID trial evaluated octreotide LAR 30 mg in comparison with placebo, the National Comprehensive Cancer Network guidelines recommend either 20 mg or 30 mg of octreotide LAR as reasonable choices for initial dose [2,6]. Other retrospective studies have shown that there is even larger variability in current clinical practice, with doses as low as 10 mg being used [14]. This is particularly important because our study showed significant differences in survival according to octreotide LAR dosage levels.…”
Section: Discussionmentioning
confidence: 71%
“…However, potential side effects may occasionally develop and need to be considered, as many patients are treated with these compounds for a prolonged period (Table 3). When symptom control is inadequate, top-up doses of 50-100 ÎŒg (up to 1000 ÎŒg) of short-acting octreotide s.c. can be given or alternatively the frequency or dose of long-acting SSA administration can be increased (Rubin et al 1999, Strosberg et al 2014. In an initial prospective study, 28 patients with CS with disease progression during therapy with octreotide LAR 30 mg every 28 days exhibited complete and partial control of symptoms after octreotide LAR 30 mg administration every 21 days in 40 and 60% of the cases, respectively; circulating biomarkers were significantly decreased in 30% (Ferolla et al 2012).…”
Section: :9mentioning
confidence: 99%
“…Studies on long-acting analogues demonstrate a symptomatic response rate of 70% (50) in patients with the carcinoid syndrome, and referring specifically to flushing, a response rate of 50-60% (51,52). Since the goal of improving symptom control is a common reason for somatostatin analogue dose escalation, Strosberg et al have recently evaluated the effects of above-standard dose of octreotide LAR in a multicentre study, concluding that the resolution or improvement of flushing after dose escalation can be observed in 80% of patients (53). When no symptomatic control is achieved, another option of treatment would be the novel multireceptor-targeted somatostatin analogue pasireotide (previously known as SOM230).…”
Section: Carcinoid Syndromementioning
confidence: 99%